Treating addiction : a guide for professionals - Miller, William R. (William Richard); Forcehimes, Alyssa; Zweben, Allen, 1940- (New York The Guilford press, 2019)
"This widely respected text and practitioner guide, now revised and expanded, provides a roadmap for effective clinical practice with clients with substance use disorders. Specialists and nonspecialists alike benefit from the authors' expert guidance for planning treatment and selecting from a menu of evidence-based treatment methods. Assessment and intervention strategies are described in detail, and the importance of the therapeutic relationship is emphasized throughout. Lauded for its clarity and accessibility, the text includes engaging case examples, up-to-date knowledge about specific substances, personal reflections from the authors, application exercises, reflection questions, and end-of-chapter bulleted key points"--
Includes bibliographical references (pages 423-503) and index.
Keywords: Substance abuse -- Treatment; Drug abuse -- Treatment